2009
DOI: 10.1167/9.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Attentive and pre-attentive aspects of figural processing

Abstract: Here we use the steady-state visual evoked potential (SSVEP) to study attentive versus non-attentive processing of simple texture-defined shapes. By "tagging" the figure and background regions with different temporal frequencies, the method isolates response components associated with the figure region, the background region, and with non-linear spatio-temporal interactions between regions. Each of these response classes has a distinct scalp topography that is preserved under differing attentional task demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 41 publications
2
36
1
Order By: Relevance
“…Although these small changes were characterized predominantly as reductions in signal lag, we note that at lower contrasts (Di or at low frequencies (Di Russo & Spinelli, 2002) the effects are similar to those we observe here. In addition, Appelbaum and Norcia (2009) recently reported a 6-ms delay in their SSVEP data caused by feature-based attention using a paradigm very similar to ours.…”
Section: Effects Of Attention On Luminance and S-cone Responsessupporting
confidence: 81%
“…Although these small changes were characterized predominantly as reductions in signal lag, we note that at lower contrasts (Di or at low frequencies (Di Russo & Spinelli, 2002) the effects are similar to those we observe here. In addition, Appelbaum and Norcia (2009) recently reported a 6-ms delay in their SSVEP data caused by feature-based attention using a paradigm very similar to ours.…”
Section: Effects Of Attention On Luminance and S-cone Responsessupporting
confidence: 81%
“…Additionally, attention enhances change detection (Hollingworth, 2004; Irwin & Zelinsky, 2002; Rensink et al, 1997; Scholl, 2000; Wolfe, Reinecke, & Brawn, 2006). Moreover, many studies have demonstrated that the amplitude of visual evoked potentials and SSVEP waveforms can be modulated by attention (Anllo-Vento & Hillyard, 1996; Appelbaum & Norcia, 2009; Appelbaum, Wade, A. R., Pettet, M. W., Vildavski, V. Y., & Norcia, A. M., 2008; Hillyard et al, 1997; Mangun, 1995; Morgan et al, 1996; Müller & Hillyard, 2000). Importantly, within the VWM literature, several experiments have directly examined the influence of attention during VWM encoding (for recent reviews see (Gazzaley, 2011; Gazzaley & Nobre, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The SSVEP is an electrophysiological signal derived from the EEG in response to temporally-periodic stimuli (i.e., stimuli flickering at a specific rate). In research investigating human cognition (e.g., visual attention), the SSVEP has been most commonly considered in the frequency domain and is used specifically when analyzing signal power in the EEG at frequencies associated with the flicker rates of experimental stimuli (Appelbaum & Norcia, 2009; Hillyard et al, 1997; Morgan, Hansen, & Hillyard, 1996; Muller & Hubner, 2002; Muller et al, 1998). One simple way to 9 conceptualize the SSVEP is that a flickering stimulus will produce an EEG signal with increased power at the flicker frequency and/or one of its harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article. ) and not the background (Appelbaum and Norcia, 2009). As noted above, prior research indicates that neurons in both V4 and the LOC are tuned for shape attributes.…”
Section: From Representation To Decisionmentioning
confidence: 99%
“…In the interest of brevity, we provide an overview of these methods, and reference the reader to our previous work (Ales and Norcia, 2009;Appelbaum and Norcia, 2009;Appelbaum et al, 2006Appelbaum et al, , 2008 for a more a more detailed description.…”
Section: Eeg Recordingmentioning
confidence: 99%